Calcium Phosphate/Hyaluronic Acid Composite Hydrogels for Local Antiosteoporotic Drug Delivery - Svarca, Alise; Grava, Andra; Dubnika, Arita; Ramata-Stunda, Anna; Narnickis, Raimonds; Aunina, Kristine; Rieksta, Eleonora; Boroduskis, Martins; Jurgelane, Inga; Locs, Janis; Loca, Dagnija (Frontiers in Bioengineering and Biotechnology, 2022)
Despite the bone ability of self-regeneration, large bone defects require surgical intervention. Likewise, if it comes to osteoporotic bone fractures, new approaches should be considered as a supportive mechanism to the surgery. In recent years more and more attention has been attracted to advanced drug delivery systems for local osteoporosis treatment, combining appropriate biomaterials with antiosteoporotic drugs, allowing simultaneously to regenerate the bone and locally treat the osteoporosis. Within the current research hyaluronic acid/strontium ranelate (HA/SrRan), HA/calcium phosphate nanoparticles (HA/CaP NPs) and HA/CaP NPs/SrRan hydrogels were prepared. Effect of CaP and SrRan presence in the composites on the swelling behaviour, gel fraction, molecular structure, microstructure, SrRan and Sr2+ release, as well as in vitro cell viability were evaluated. Obtained results revealed that the route of CaP nanoparticle incorporation into the HA matrix had a significant effect on the hydrogel gel fraction, rheological properties, swelling behaviour and microstructure. Nevertheless, it had negligible effect on the release kinetics of SrRan and Sr2+. The highest cell (3T3) viability (>80%) was observed for HA hydrogels, with and without SrRan. Moreover, positive effect of SrRan on 3T3 cells was also demonstrated, showing significant increase (up to 50%) in cell viability if the used concentrations of SrRan were in the range of 0.05 - 0.2 µg/mL.